2015
DOI: 10.1007/s13201-015-0316-9
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and quality parameters of dug and tube well water of Khipro, District Sanghar, Sindh, Pakistan

Abstract: Thirty-nine (23 dug and 16 tube well) samples were geochemically evaluated and investigated to ascertain the quality of water in Khipro, Sindh. The analytical results exhibited abundance of major cations and anions in Na ? [ Ca 2? [ Mg 2? [ K ? and Cl-[ HCO 3-[ SO 4 2sequence. Stiff diagram showed dug well sample have high Na-Cl and moderate Mg-SO 4 content as compared to tube well samples. Majority of dug well samples appeared as Na-Cl type on Piper diagram while tube well samples are mixed type. Gibbs diagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Groundwater is affected by Na + , Ca 2+ , Mg 2+ and HCO 3 − substances in water and soil. The measure for considering the permeability of water for crops is based on PI (Bashir et al, Huda, Naseem, Hamza, & Kaleem, 2015). The PI is determined as follows:…”
Section: Permeability Index (Pi)mentioning
confidence: 99%
“…Groundwater is affected by Na + , Ca 2+ , Mg 2+ and HCO 3 − substances in water and soil. The measure for considering the permeability of water for crops is based on PI (Bashir et al, Huda, Naseem, Hamza, & Kaleem, 2015). The PI is determined as follows:…”
Section: Permeability Index (Pi)mentioning
confidence: 99%
“…In this study, the water quality of the Amarapura Aquifer was examined to determine if the main source of pollution is wastewater. Na-Cl water types have been observed in many groundwater systems that were contaminated with urban wastewaters (Bashir et al 2015;Hassane et al 2016;Lee et al 2010). In this study, Na-Cl water types were observed, and water quality parameters determined elevated levels of total dissolved solids, electrical conductivity, chloride, nitrate, ammonium, and E. coli.…”
Section: Water Quality and Wastewatermentioning
confidence: 72%
“…Figure 4d shows a positive relationship between Na + and Cl − concentrations, with all water samples plotting above the 1:1 line. This indicates that most of the Na + is captured along water flows poor in Cl − [18]. In Figure 4e, Na + +K + increases in parallel with Cl − + SO4 2− , hinting at a common source for these ions and by extension to the presence of Na2SO4 and K2SO4 Salts [1].…”
Section: Sources and Processes Controlling Ion Compositions Of The Lakesmentioning
confidence: 86%
“…The isotope ratios are reported as per mil deviation (δD, δ 18 O or δ 37 Cl) of the D/ 1 H, 18 O/ 16 O ratios relative to SMOW (H and O isotope systematics) and ISL-354 standards (Cl isotopes), according to the equations:…”
Section: Sample Preparation (δ 37 Cl)mentioning
confidence: 99%
See 1 more Smart Citation